FREQUENCY OF STONE CLEARANCE AFTER TRANSURETHRAL FRAGMENTATION OF LARGE URINARY BLADDER CALCULI USING PNEUMATIC SWISS LITHOCLAST - Shawana Asad,; Bilawal Gul,; Mir Jalal-ud-din,; Sher Ali Khan,; Rabeeha Bashir,; Hina Rafaqat, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Vesical calculi refer to stones in the urinary bladder. The causes of bladder stones include bladder outlet obstruction, neurogenic voiding dysfunction, infection, or foreign bodies. Very rarely, these vesical calculi may reach very large sizes and the largest dimension can sometimes reach 13 centimeters. Methods: This descriptive cross-sectional study was conducted from 1ST May 2019 to 31st October, 2019 at Institute of Kidney Diseases, Urology Department, Hayatabad Peshawar. 164 patients with vesical stone were included in study. Ultrasound-KUB was used for diagnosis of vesical stone and after informed consent, and they underwent transurethral nephroscopic lithotripsy via the pneumatic Swiss Lithoclast. Results: Frequency of stone clearance was 96.34%. No statistically significant association of stone clearance was observed with age, gender, number of stones or max dimension of largest stone in the bladder (p > 0.05). Conclusion: Transurethral nephroscopic pneumatic lithotripsy via pneumatic Swiss Lithoclast is safe and effective procedure for treatment of large vesical stones. However, this being the first such study in adults, more data is needed to confirm these findings.